1986
DOI: 10.1029/jb091ib07p07403
|View full text |Cite
|
Sign up to set email alerts
|

A magnetotelluric survey over the East Bull Lake gabbro‐anorthosite complex

Abstract: Tensor and scalar magnetotelluric and audiomagnetotelluric (MT/AMT) data have been acquired on a gabbro-anorthosite pluton in northern Ontario, about 100 km west of Sudbury. The scalar data from 102 sites were used to map resistivity contrasts associated with near-surface geology and overburden. Data from stations located away from possible geological inhomogeneities provided a structural interpretation which was subsequently confirmed by tensor MT soundings and by drilling. The scalar data also provided a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Resistivities of greater than 30000 Q . m for the gabbro-anorthosite agree with the results of Kurtz et al (1986) for the Paleoproterozoic East Bull Lake gabbroanorthosite. Even higher resistivities in the centre of the Lac Bouchette gabbro -anorthosite may indicate the presence of a core of more anorthositic rock, mapped to the west of the profile (Fig.…”
Section: Conductive Zonessupporting
confidence: 85%
“…Resistivities of greater than 30000 Q . m for the gabbro-anorthosite agree with the results of Kurtz et al (1986) for the Paleoproterozoic East Bull Lake gabbroanorthosite. Even higher resistivities in the centre of the Lac Bouchette gabbro -anorthosite may indicate the presence of a core of more anorthositic rock, mapped to the west of the profile (Fig.…”
Section: Conductive Zonessupporting
confidence: 85%
“…The continental crust in many areas of the world is characterized by a significant increase in electrical conductivity at mid to lower crustal depths (Jones 1981). Studies by Dowling (1970), Koziar & Strangway (1978), Sternberg (1979), Connerney, Nekut & Kuckes (1980), Duncan et al (1980), Kurtz (1982), and Kurtz, Ostrowski & Niblett (1986) have shown this to be the case for Shield regions of North America. The cause of the enhanced conductivity has not been firmly established and theories range from concentrations of specific mineralogical assemblages such as graphite to the presence of free water or other fluids.…”
Section: Introductionmentioning
confidence: 90%
“…. 'macro-anisotropy' (Cull 1985;Kurtz, Ostrowski & Niblett 1986;Junge, Schmucker & Tezkan 1991). Simulating anisotropy with the dykes striking east-west ( Fig.…”
Section: T W O -D I M E N S I O N a L Effectsmentioning
confidence: 99%